The Effectiveness of Jumping Rope Training on the Speed and Reaction of U-15 Female Badminton Players - Isauraya, Fatikha; Suratman, Suratman; Pratama, Rivan Saghita (Indonesian Journal of Physical Education and Sport Science, 2025)
Studi purpose. This study aims to determine the differences in speed and reaction between female teenage athletes and non-athletes 15 year-old. Materials and methods. This study used a quantitative approach with a comparative design. The research sample consisted of 20 adolescent girls who were divided into two groups, namely the athlete group and the non-athlete group. The athlete group consisted of 10 girls who were athletes of PB. Ngudi Berkah and have done skipping rope training regularly three times a week with a duration of 15-20 minutes, for four weeks before data collection whereas, the non-athlete group amounted to 10 adult Taman Junior High School students who did not take part in sports training and did not do skipping rope exercises. The data collection instruments include a 20-meter sprint test to measure speed and a Whole-Body Reaction test to measure reaction time. Results. Statistical analysis showed that the athlete's group significantly outperformed the non-athletes' group in terms of speed (p = .000) and reaction time (p = .001). These findings suggest that jump rope training effectively improves key performance components in young badminton athletes Conclusions. Skipping rope exercises are effective in improving speed and reaction, with speed being the more dominant aspect that distinguishes athletes from non-athletes. This exercise can be incorporated into the physical training program for badminton athletes. The results of this study underscore the importance of incorporating jump rope training into structured training program to support early physical development in youth sports.